Co-occurrence of harmful algal blooms and whale deaths - Silber, Gregory K.; Silber, Katy M. (Frontiers in Marine Science, 2024)
Marine harmful algal blooms (HAB) have been implicated in marine mammal die-offs; but the relationship between sub-lethal algal toxicity and marine mammal vulnerability to human activities has not been assessed. HAB toxins can result in compromised neurological or muscular systems and we posit these conditions can expose marine mammals to increased likelihood of entanglement in commercial fishing gear or ship strike. To investigate whether HABs and large whale injuries and deaths were associated, we assessed the spatiotemporal co-occurrence of HAB events and large whale mortalities/injuries in U.S. east (from 2000-2021) and west (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021) coastal waters. The number of mortalities/injuries was frequently higher in years with large-scale or severe HABs. We found statistically significant relationships between the occurrence of HABs and whale mortalities/injuries in west coast waters –at least three additional whale deaths/injuries were detected near an active HAB than in areas where a HAB was not reported. This relationship was similarly positive but weaker for east coast waters, a difference that may be attributable to differing oceanographic features, or approaches used in whale data collection, between coasts. Saxitoxin-producing Alexandrium was the most common causative agent on both the east (64.1%) and west (57.8%) coasts; and domoic acid-producing Pseudo-nitzschia was more common along the west (33.3%) than the east coast (8.7%). Algal toxins can be entrained in marine ecosystems, including in whale prey, and can chronically persist in marine mammals. Given many whale deaths/injuries resulted from fishing gear entanglement and vessel strikes, algal-induced morbidities may diminish whale capacities to detect or avoid fishing gear and approaching vessels. While there was much interannual variability, general increasing trends were observed in both whale death/injury and HAB datasets which may be attributable to increased monitoring or rising ocean temperatures. HAB prediction modeling has become increasing sophisticated and could be used as a tool to reduce whale mortality by limiting human activities (e.g., curtailing fishing operations) when HABs, whale occurrence, and maritime activities are expected to overlap. Additional systematic data collection is needed to track and model mechanisms underlying relationships between HABs and incidental whale mortality.